Sikap Orang Tua Terhadap Kekerasan Anak Akibat Media Sosial - Estiningtyas, Nuraini; , Susatyo Yuwono, S.Psi. M.Si. Psi (2016)
This study aimed to describe the attitude of parents towards child abuse as a result of social media. This study used a qualitative approach, data collection using semi-structured interview technique. Subjects in this study were selected by purposive sampling techniques snowball sampling basis, amounted to 2 parents either father or mother with the criteria of having a child aged 12-18, educated, less educated, earn above the minimum wage, earned below the minimum wage, child ever have been victims of violence because of social media. The results of this study found that parental attitudes toward child abuse as a result of social media tend to be negative. The negative attitude of parents of child abuse as a result of social media is formed by the belief of parents that the development of social media to deteriorate, a lot of violence going on in social media or social media as a result, the negative impact of social media more and better social media users aged above 18 years. Parents are also concerned with the many victims of violence because of social media, concerned and sad because a lot of people are losing time for social media, angry with the doer of child abuse. So that parents tend to act in a way to follow the development of social media, equip children with the knowledge of religion and general knowledge, monitoring and control in children. Another interesting finding of this study is parents with higher education that their children become victims of violence because of social media remained supportive of children using social media for the means to develop themselves in a way to equip themselves with the knowledge and development of children at this time.